American encounters with Arabs : the "soft power" of U.S. public diplomacy in the Middle East - Rugh, William A. (Praeger Security International, 2006)
For sixty years, U.S. government officials have conducted public diplomacy programs to try to reach Arab public opinion--to inform, educate, and understand Arab attitudes. American public affairs officers have met serious challenges in the past, but Arab public criticism of the United States has reached unprecedented levels since September 11, 2001. Polls show that much of the negative opinion of the United States, especially in the Middle East, can be traced to dissatisfaction with U.S. foreign policy. Rugh, a retired career Foreign Service officer who twice served as ambassador to countries i.